The association of organizational justice views and turnover intent among correctional staff - Lambert, Eric G. (Criminal justice studies, 2023)
Fairness is a core concept in U.S. society, including in the workplace. Organizational justice theory holds that workers expect to be treated in a fair and just manner and that higher levels of organizational justice usually result in lower levels of withdrawal work behaviors, such as absenteeism and turnover intent, while lower levels of organizational justice perceptions are associated with higher engagement in withdrawal behaviors. The current study examined the relationship between organizational justice views, specifically distributive and procedural justice, and turnover intent, while controlling for the personal characteristics of age, gender, position, tenure, educational level, and marital status and the work variables of job stress and job involvement. Using the responses from 322 employees from a state prison located in the Southern region of the United States, procedural justice was observed to have a significant negative association with turnover intent, but distributive justice had a nonsignificant relationship. Job stress was associated with a significantly higher level of turnover intent, while job involvement was significantly associated with lower turnover intent. Among the personal characteristics, only age had a significant association, with older workers expressing lower turnover intent.